KEMAMPUAN KEUANGAN DAERAH KABUPATEN TABALONG DALAM OTONOMI DAERAH - Muzdalifah Muzdalifah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2013)
The objective of this research is to analyze financial capacity of the district Tabalong the indicators measure financial capacity are the independency ratio and the index of financial capacity that used by Bappenas. The financial secondary data is used during 2002-2011. The results show that the average ratio of independence 6,58 % under 25 % in relationship pattern instructive which means that still depends on the central government same with the result of average for the ability of the financial index 0,51 which means that district tabalong since the regional autonomy has not yet able to the treasury. Keywords: financial capacity, independency ratio.